Research on Multidimensional Quantitative Evaluation System of Airline Marketing Strategies - Xia, Qing; Zhu, Xiqi; Gu, Jialei; Wang, Zhiyi (Scientific Journal of Technology, 2025)
This paper constructs an evaluation system for airline marketing strategies, and quantitatively analyzes the typical strategies of airlines using fuzzy comprehensive evaluation method, analysis hierarchical method (AHP) and Topsis method. The study firstly screens strategies from product, price, channel and promotion dimensions, and obtains evaluation data from industry experts through expert scoring method. Based on the fuzzy comprehensive evaluation model, the evaluation is carried out from the first-level indexes of input cost, output benefit, and innovation drive, and the advantage score of each strategy is calculated. Then, with the help of AHP to determine the weights of the indicators, it is found that the output benefit is dominant in the evaluation of strategies, followed by the input cost. Combined with the Topsis method to rank the strategies, the results show that there are significant differences in the overall effectiveness of different strategies, with one strategy performing best by balancing costs and benefits, and the other ranking lower due to lack of innovation. This study provides a scientific and quantitative method for airlines to optimize their marketing strategy combinations and verifies the applicability of the multidimensional evaluation model in the field of airline marketing.